The scope of methodology transformation for human development management determining an increase in business effectiveness of investments in training projects - Paweł Kopijer (The Central European Review of Economics and Management (CEREM), 2019)
Aim: The aim is to show market indications with respect to how to alter training investment management so that to improve the impact of training on the organization's performance. The topic is important because the effectiveness of business practice in training processes in Polish organizations continues to be poor due to the lack of benchmarks in the form of good practices or research.~Design / Research methods: The paper cites research findings which illustrate the existing practice of training management in Polish companies, as well as studies allowing for identification of the key indications for changes. The research methods employed in the findings cited belong to the category of pragmatic methods drawing on quantitative data gathered based on a questionnaire and quantitative and qualitative data gathered on the basis of an interview. The data stemming from the research cited are obtained through a subjective interpretation of the existing processes and phenomena.~Conclusions / findings: TDI Study shows that the following are the weakest link in training processes. The area of evaluation from the perspective of assessing how the training affects the firm's performance. The area of managers' commitment during the stage of applying competences on the job. The study of Indications for Training Process Transformation shows that the crucial change for an organization in the context of improving business effectiveness of training is to shift the focus of the analysis of needs from being centered solely on the competence gap towards identifying potential impact of training on business performance. The most realistic change involves introducing tools designed for managing the implementation phase and building awareness among participants that training is not merely an element of knowledge acquirement but an obligation to change behaviors with this change yielding business advantages for the company.
Keywords: M53; 330; training policy; training effectiveness; training assessment